Nutritional value and antioxidants in fruiting bodies of Pleurotus ostreatus mushroom - Farghaly, Fatma A.; Mostafa, Eman M. (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The fresh and dried fruiting bodies of cultivated P. ostreatus are accomplished by using different chemical analytical methods. The results are showing that the nutritional value is including: energy 236.624 & 56.05 kcal/100g; moisture content 86.33 & 5.155%; also the following constitutes by g/100g DW in fresh and dry samples: dry matters 13.667 & 94.844; total proteins 22.6 & 9.6; amino acids 3.43 & 0.68; total carbohydrates 35.1 & 2.83 and total lipids 0.91 & 0.77. Each of K, Mg, Zn, Na and Cu are determined by mg/100g DW. Antioxidant metabolites are detected and included ascorbic acid 2.395 & 0.6204 g/100g DW in fresh & dry samples, respectively; free phenols are 23.99 & 163.515 and bounded phenols are 2.85 &1.96 Î¼g/100g in fresh & dry samples, respectively. Comparison between the fresh and dry P. ostreatus samples appeared that the fresh sample has high nutritional value with highest values in all tested parameters. Also the dry samples had the higher contents of four minerals (1696.25 K, 90.25 Mg, 21 Zn, and 4.5 Cu mg/100g DW comparing to the fresh sample (1402.5 K, 74.25 Mg, 18.25 Zn, and4.0 Cu). On the other side, the levels of each of Fe were 179.75 & 78 and Na 417.7 & 204.25 mg/100g DW, respectively).